Russian experience in system developing of tourist information centres: ways of application in the Republic of Belarus - Marozau, Dzmitry V. (Journal of the Belarusian State University. History, 2023)
The article analyses the problem of functioning of the system of tourist information centres (TIC) in the Russian Federation, the history of its formation, as well as the main development trends and ways of application of the Russian experience in the Republic of Belarus. Many aspects are discussed only in the professional environment, not reflected in academic publications. The basic goals and objectives of the Russian TICs and their most significant achievements are considered: formation of the non-commercial partnership «National Association of Tourist Information Organisations», creation of a special standard for TICs, development of a unified brand book, use of mobile centres, etc. We also analyse common problems: creation of conditions for unhealthy competition of centres heterogeneous in their organisational affiliation, overburdening of state centres with administrative tasks, etc. The article gives recommendations on the implementation of successful practices in Belarus: partnership of centres with gas stations, opening TICs on the basis of universities, as well as museum institutions. The article suggests ways to build professional relations between Belarusian and Russian specialists in this field: exchange of lists of the most relevant tourist events for Russians in Belarus and Belarusians in Russia, organisation of trainings for TIC employees at specialised exhibitions, forums and conferences, inviting non-commercial partnership «National Association of Tourist Information Organisations» specialists, participation of Belarusian TICs managers in the events of their Russian colleagues.